The question of the transfer of the relics of the catholic saint Andrei Bobolia prior to Polotsk celebrations in 1910: documents from the collections of the National historical archive of Russia and the National historical archive of Belarus - Viktor Koronevskii (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. II, Istorii͡a︡, istorii͡a︡ Russkoĭ pravoslavnoĭ t͡s︡erkvi, 2023)
Documents from the collections of the Russian State Historical Archives and the National Historical Archives of Belarus are considered for publication, shedding light on the discussion of history that unfolded in the highest circles of representatives of the Russian Empire in 1909–1910 about the remains of Jesuit Andrew Bobola, revered by Catholics as a holy, kept in the Dominican church of Polotsk. Actualization of the Bobola problem, whose history went back to its origins at the beginning of the 19th century, was dangerous with the preparation of the transfer of the relics of St. Euphrosyne of Polotsk. The cult of Andrew Bobola has long been used by Polotsk Dominicans to lure the Orthodox inhabitants of Polotsk into Catholicism, so the church and secular authorities of the Russian Empire feared that by appealing to the figure of Bobola, Catholics might try to spoil the ceremony of transferring the relics of St. Euphrosyne and use a great Orthodox celebration to promote their faith. In this regard, the question was raised about the fate of the remains of Andrew Bobola. Some officials believed that it would make sense to take the Catholic relic outside of Polotsk (for example, to Pinsk). However, the milder version prevailed. It was decided not to touch the remains of Bobola, so as not to give Catholics an extra reason for propaganda and exaltation of him as a saint. The following documents are published: presentation of the Vitebsk Governor B.B. Gershau-Flotov addressed to the Minister of Internal Affairs P.A. Stolypin on the desirability of transferring the Catholic relic from Polotsk; a fragment of the most obedient report on the state of the Vitebsk province for 1908, in which the same idea is defended; the initial response of the Minister of the Interior to B.B. Gershau-Flotov; minutes of a meeting of a special meeting convened on the initiative of Nicholas II and designed to decide the fate of Bobola's remains.